631 A Comparison of the Microbiology Profile for Two-Stage Revision Surgery in Periprosthetic Joint Infection (PJI) of Primary Knee Arthroplasty and Lower Limb Endoprostheses for Tumour Surgery. (19th August 2022) - McCulloch, RA; Adlan, A; Jenkins, N; Parry, M; Stevenson, J; Jeys, L
Abstract: Aim: To compare the microbiology organisms responsible for PJI in patients who underwent two-stage revision of infected primary knee replacement with two-stage revision of infected oncological endoprostheses of the lower limb in a single institution. Method: 118 patients were treated with 2-stage revision surgery for infected knee arthroplasty and lower limb endoprostheses between 1999 and 2019. 74 patients had two-stage revision for PJI of knee arthroplasty and 44 had two-stage revision to eradicate infection of lower limb endoprostheses for tumour resection. All microbiological data from the first stage sampling was collected and analysed retrospectively. Patient host and extremity criteria were categorised according to the MSIS Host and Extremity Staging System. Results: According to the MSIS Staging System, the host and extremity grade of the knee arthroplasty PJI cohort were significantly better than endoprostheses PJI(p<0.05). The incidence of multi-drug resistance (MDR) was higher, 36% in the endoprosthetic group compared to 17% in the infected primary knee replacement group (p=0.001). MDR was most common in coagulase-negative staphylococcus. Gram-positive organisms were isolated in more than 80% of cultures from both cohorts. Coagulase-negative staphylococcus (CoNs) was the commonest gram-positive organism and E Coli was the commonest Gram-negative organism in both groups. Conclusion: Patients presenting with PJI after lower limb endoprostheses have a higher incidence of MDR organisms compared to an arthroplasty cohort. Pre-operative microbiological sampling and meticulous sampling methods intra-operatively are extremely important in these patients.